ICT Industries and Smart Cities: South Korea as Technological Link with Latin America - Bavoleo, Bárbara Inés (2020)
In recent years, South Korea has become a world benchmark in e-Government, ICT policies and Smart Cities, and has pursued a strong policy of assistance and consultation aimed especially at developing countries. In 2010, 2012 and 2014, South Korea ranked first in the world ranking of egovernment carried out by the United Nations Public Administration Network (UNPAN). The country has managed to maximize the use of information and communications technologies in public administration to such an extent that practically any procedure can be carried out online. Examples of this are: Korea On-Line E-Procurement System (KONEPS), a single portal to obtain information on contracts, tenders, acquisitions and payments of all administrative organizations) (see Image 1), Korea Immigration Smart Service (KISS), customs procedures (UNIPASS) and patents (KIPOnet), among others. The private sector played a critical role in developing innovative technologies and systems to meet the challenges of digitizing official documents and the state's interaction with citizens. Korean civil society is also very active on a virtual level when it comes to exchanging information, which is why it has, for example, the E-people portal to channel queries from those who do not know to which government agency submit their complaints or want to participate in collective discussions / petitions on political issues.